2022
DOI: 10.1002/jum.15963
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Abdominal Cystic Masses

Abstract: Objectives To assess the diagnostic accuracy of prenatal ultrasound in detecting intra‐abdominal masses derived from different systems. Methods Fetuses diagnosed with abdominal cystic masses during prenatal ultrasound were included in this study. The basic biological parameters of the fetus were measured in addition to the location of the cystic mass, the shape and size of the mass, the thickness of the cystic wall, dynamic changes, blood supply of the mass, and relationship with the surrounding organs. Whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…According to the literatures [18,21–23] and the above experimental facts, a possible reaction mechanism is deduced (as shown in Scheme 2). During the reaction, the formation of an ethoxylate anion initially occurred in situ by the deprotonation of a molecule of ethanol on the cathode.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…According to the literatures [18,21–23] and the above experimental facts, a possible reaction mechanism is deduced (as shown in Scheme 2). During the reaction, the formation of an ethoxylate anion initially occurred in situ by the deprotonation of a molecule of ethanol on the cathode.…”
Section: Resultsmentioning
confidence: 96%
“…[21] Moreover, electrochemical synthesis has also made a lot of progress in practical applications, such as the electrochemical synthesis of spirodihydrofuran and cyclopenta[b]pyran derivatives. [22][23] Both of the above reactions are initiated by an active base, which is generated by the transfer of electrons from the cathode to the substrate or solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that MRI serves as a valuable supplementary tool to prenatal ultrasound, enhancing diagnostic accuracy with a reported rate of 73.4% [ 11 ]. However, studies have shown that cystic masses of the gastrointestinal tract can be accurately diagnosed in 91.1% of cases, using prenatal ultrasound [ 12 ].…”
Section: Discussionmentioning
confidence: 99%